Using Technology to Teach Character to Middle School Students - Butler, Lara (My University, 2005)
The purpose of this action research study was to determine whether a web-based character education program had any effect on middle-grade students' knowledge of character traits and the students' behaviors. Also, the use of a web-based character education curriculum as an effective instructional methodology for teaching character education was examined. The intervention, which included web-based character education lessons integrated with classroom discussions, projects, and activities, was presented to 25 eighth-grade language arts students. Data were collected through pretest and posttest of character traits, attitudinal surveys, and interviews with the students and the teacher. Findings indicated that students' knowledge of character traits did increase. Students and the teacher also reported an increase in positive student behaviors throughout the intervention. Results of the student interviews revealed that students enjoyed using the character education Website, participating in activities such as writing letters to the soldiers, and learning about organizations within their community that promoted good character. Additionally, students stated that class discussions paired with the Web-based lessons helped to reinforce their learning of the character traits. The results of the study were communicated to the learning community through a celebration with the students, teacher, and administrators. The results of the action research study were also shared with the county curriculum coordinator.
Keywords: Web-Based Character Education Program; Middle Grade Education